Implementasi Prinsip-prinsip Sustainable Development Pada Ekowisata Bukit Matang Kaladan Desa Tiwingan Lama Kabupaten Banjar - Kamilazzahra, Ahyati; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2024)
Theoretically, ecotourism development is an effective means of realizing sustainable development. This research aims to analyze efforts to develop ecotourism at Matang Kaladan Hill in Tiwingan Lama Village, Banjar Regency. using the perspective of sustainable development theory (Burger). The research approach used is qualitative, and is a case study type of research. Data collection was carried out through participant observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model. The research results show that the development of Bukit Matang Kaladan ecotourism has manifested several principles of sustainable development. First, ecological protection in the form of: 1) nature conservation programs; 2) prohibition on cutting down trees in conservation forest areas; 3) prohibition of littering. Second, social development in the form of: 1) growing tourism awareness among local communities based on the 7 (seven) sapta charm values; 2) increasing the level of public education. Third, economic development can be seen in: 1) the existence of original village income originating from ecotourism; 2) increasing employment opportunities for the community. However, the development of Bukit Matang Kaladan ecotourism cannot be said to have implemented the principles of sustainable development optimally and comprehensively. One of them is the principle of sustainable development, the point of ecological sustainability, which can be seen in the local community of Tiwingan Lama Village and tourists who do not keep the environment clean properly. The behavior of littering causes large amounts of plastic waste to be scattered in the Bukit Matang Kaladan ecotourism area. Therefore, it is hoped that the village government will continue to make efforts related to optimal ecological sustainability in the field of plastic waste management.